Systematic Literature Review: Determinan Brand Trust Perguruan Tinggi Melalui Brand Image Dengan Akreditasi Sebagai Variabel Moderasi - Pramesti Nurul Adinda; Hapzi Ali (Journal of Applied Accounting And Business, 2026)
The study aims to analyze factors affecting university brand trust through brand image with accreditation as a moderating variable. The research object is higher education institutions in the context of educational marketing. The method used was a systematic literature review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines through literature searches in Google Scholar and scopus for the period 2021–2026. Based on the selection process, 15 articles met the inclusion criteria. The results showed that campus facilities, campus activities, alumni influence, digital marketing, and tuition fees positively affect university brand image. Furthermore, brand image significantly affects brand trust, while accreditation strengthens the relationship between brand image and brand trust. In conclusion, improving university brand trust requires integrated strategies through service quality enhancement, student experience, alumni reputation, digital marketing, affordable tuition, and stronger accreditation.